The Effects of Self-Efficacy and Family Support Promotion Program on Overweight among Junior High School Students - รุ่งโรจน์วัฒนา วาสนา; คมพยัคฆ์ จริยาวัตร; พันธสี พรศิริ (Journal of The Royal Thai Army Nurses, 2019)
The study aimed to investigate the effects of self-efficacy and family support promotion program on overweight among junior high school students by using Quasi-Experimental Research Designs, two group pretest-posttest to examine. The sample were overweight Mathayomsuksa II students. 60 student which are 30 student for control group and 30 students for experimental group. The instruments were the body weight record and the food consumption and physical activity questionnaire. The questionnaire was evaluated for content validity by three experts. CVI was 0.84. Cronbach’s alpha coefficient was 0.75. The statistics utilized for analysis were descriptive statistics; chi-square, and t-test (p < .05) The result showed that after participating in the self-efficacy and family support promotion program, The experimental group had higher average scores of food consumption and physical activity behaviors with the statistical significance at the p-value of .002 and .001 respectively. The scores were more than those of the control group, but they were not statistical significant with the p-value of .655 and .863 respectively. Finally, after participating in the program, the number of overweight students also decreased. Health-promoting personnel could apply this program by working cooperatively with the teacher in order to apply this program in classroom teaching.